Obrzędy sakramentu małżeństwa w ujęciu wymogów Kodeksu Prawa Kanonicznego z 1983 roku - Kilanowicz, Ryszard (Ius Matrimoniale, 2019)
The liturgy of the Church is an expression of his life with Christ, it uses natural signs such as: wine, water, light, fire, smoke, oil, salt, and ash. It is through Christ, that they are given new meaning. This meaning is to glorify God and sanctify man. The sacramental ordinances are determined by ecclesiastical law which follows the nature and life of the Church. The ordinances of the Church, through the visible, direct us to the invisible. Behind what is visible there is no action or God's grace. These signs of God's presence are symbols, which St. Augustine calls the encounter between God and man in the world of signs and symbols, a Sacrament. The sacraments of the Church are graces given by God to man for his sanctification. In sacramental rites, the Church can change form, but never in essence and matter. The matter of the sacrament of marriage is between a woman and a man. The rites of the sacrament of marriage, were announced in 1969, are used in Poland, however, it has been adapted to the new Code of Canon Law of 1983. Jesus instituted the sacrament of marriage. Marriage should be celebrated at Holy Mass and is characterized by unity and indissolubility. During the rites of the sacrament of marriage, the Church then asks what is the will of the person is for getting married. The couple then join their right hands and place the wedding rings on each other’s ring finger. The effects of the sacrament of marriage, which express the Rites of the Sacrament of Marriage, are: marriage community, grace and family. The liturgy with the sacrament of marriage speaks of the sanctity of marriage through the beauty of its celebration.